On the links between mathematical software package Mathcad and Excel - Sėrikovienė, Silvija (Lietuvos matematikos rinkinys, 2001)
The paper describes how to use dynamical links between Mathcad and Excel components. The usage of such dynamical data exchange is presented by solving of transportation problem.